2009
DOI: 10.1007/s12551-009-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

New factors contributing to dynamic calcium regulation in the skeletal muscle triad—a crowded place

Abstract: Skeletal muscle is a highly organized tissue that has to be optimized for fast signalling events conveying electrical excitation to contractile response. The site of electro-chemico-mechanical coupling is the skeletal muscle triad where two membrane systems, the extracellular ttubules and the intracellular sarcoplasmic reticulum, come into very close contact. Structure fits function here and the signalling proteins DHPR and RyR1 were the first to be discovered to bridge this gap in a conformational coupling ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Even though the molecular identity of the permeation pathway remains a matter of some debate [3,4], the voltage-sensor for activation of ECCE is by definition housed in Ca V 1.1. For this reason, any physiological impact of ECCE is directly controlled by Ca V 1.1.…”
Section: Excitation-coupled Ca2+ Entry and Cav11mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the molecular identity of the permeation pathway remains a matter of some debate [3,4], the voltage-sensor for activation of ECCE is by definition housed in Ca V 1.1. For this reason, any physiological impact of ECCE is directly controlled by Ca V 1.1.…”
Section: Excitation-coupled Ca2+ Entry and Cav11mentioning
confidence: 99%
“…Moreover, Ca V 1.1 requires the influence of the type 1 ryanodine receptor (RyR1) to support its L-type channel function. However, the physiological significance of L-type Ca 2+ current via Ca V 1.1 is uncertain [3,4], and the ability of Ca V 1.1 to carry out its most important function does not depend on Ca 2+ flux at all [5,6]. …”
mentioning
confidence: 99%
“…That entry was a small rectifying highly Ca 2+ selective current, not affected by Ca 2+ channel blockers (Hoth and Penner, 1992) called Ca 2+ Release Activated Ca 2+ Current (I CRAC ). Two research groups then identified in 2005 the Stromal Interacting Molecule (STIM) as a single-pass transmembrane EF-hand protein that acts as Ca 2+ sensor in the endoplasmic reticulum lumen of many cells with a low affinity of ~200-600 μM (Liou et al, 2005;Roos et al, 2005;Zhang et al, 2005;Stathopulos et al, 2006;Canato et al, 2010;Friedrich et al, 2010). In 2006 it was confirmed the interaction of STIM with a protein in the plasma membrane called Orai, which constitutes the transmembrane pore of the CRAC complex (Vig et al, 2006b(Vig et al, , 2006aFeske et al, 2006;Prakriya et al, 2006;Soboloff et al, 2006;Hou et al, 2018).…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Most importantly the α1S‐subunit serves as voltage sensor in excitation–contraction coupling [ 50 , 51 , 52 ], but also functions as an L‐type Ca 2+ ‐channel which allows ECCE [ 62 ]. Of note, multiple signalling interactions occur in a bidirectional way at the triad junction between the transverse tubular L‐type Ca 2+ ‐channel and the Ca 2+ ‐release channel of the sarcoplasmic reticulum [ 63 ]. On the one hand, depolarisation‐induced conformational changes in the voltage‐sensing L‐type Ca 2+ ‐channel translate into opening of the Ca 2+ ‐release channel in the sarcoplasmic reticulum during orthograde signalling that regulates excitation–contraction coupling [ 64 ].…”
Section: Excitation–contraction Coupling and Calcium Homeostasis In S...mentioning
confidence: 99%